The investigation and isolation of histamine in fish performing microwave-assisted extraction (MAE) and analyzed using liquid and gas chromatography - Evi, Rahmawati; Muhammad Abdurrahman, Munir; Fitria, Rahmawati; Adhi, Gunawan (AIP Publishing, 2025)
Histamine is a compound that is related to food poisoning. The FDA has warned that histamine compound is acceptable below 50 mg·kg−1. For this reason, a swift, robust, and precise approach is required. To reach the criteria, chromatography methods have been applied, such as liquid chromatography (LC) equipped with fluorescence detector (FLD) and gas chromatography (GC) with mass spectrometry (MS). Histamine in fish samples was satisfactorily isolated with trichloroacetic acid (TCA) using microwave-assisted extraction (MAE). In terms of validation, the excellent linear range obtained between 10−3 – 10−1 nmol‧L−1, satisfactory recovery at level 0.1 nmol‧L−1 attained with detection limit at 0.01 nmol‧mL−1. The validated methods were successfully applied to analyze histamine in fish samples. The MS detector was also successfully used to determine the molecular weight of histamine in fish tuna (Thunnus sp.).